Water quality dynamics in an urbanizing subtropical estuary(Oso Bay, Texas). Issue 1 (15th March 2016) - Wetz, Michael S.; Hayes, Kenneth C.; Fisher, Kelsey V.B.; Price, Lynn; Sterba-Boatwright, Blair
Abstract: Results are presented from a study of water quality dynamics in a shallow subtropical estuary, Oso Bay, Texas, which has a watershed that has undergone extensive urbanization in recent decades. High inorganic nutrient, dissolved organic matter and chlorophyll concentrations, as well as low pH (< 8), were observed in a region of Oso Bay that receives wastewater effluent. Despite being shallow (< 1 m) and subjected to strong winds on a regular basis, this region also exhibited episodic hypoxia/anoxia. The low oxygen and pH conditions are likely to impose significant stress on benthic organisms and nekton in the affected area. Signatures of eutrophied water were occasionally observed at the mouth of Oso Bay, suggesting that it may be exported to adjacent Corpus Christi Bay and contribute to seasonal hypoxia development in that system as well. These results argue for wastewater nutrient input reductions in order to alleviate the symptoms of eutrophication. Highlights: Results are presented from a water quality study in an urbanizing subtropical estuary, Oso Bay, TX. Symptoms of eutrophication were observed in an area of Oso Bay that receives wastewater effluent. Eutrophied water may be exported to a region of Corpus Christi Bay that has episodic hypoxia. Wastewater nutrient inputs will need to be reduced to alleviate the symptoms of eutrophication.